Perlindungan Hak Cipta Terhadap Pembajakan Film Nasional - Grivti M Asthenu; Teng Berlianty; Muchtar Anshary Hamid Labetubun (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Exclusive rights related to economic rights and moral rights that will be attached automatically to a work created without having to register.Purposes of the Research: Analyze the form of legal protection for national film copyright holders and the process of preventing film piracy that occurs in Indonesia. Methods of the Research: The research method used in writing this thesis is normative legal research or library research, namely, legal research conducted by examining primary, secondary and tertiary legal materials.Results of the Research: The form of legal protection for national film copyright holders is guaranteed by the existence of a set of laws and regulations that function as a government tool in carrying out preventive and repressive efforts, especially for film copyright violators. The process of preventing film piracy is by registering copyright in order to obtain legal protection / legal certainty for the rights of his creations. This is an effort of Preventive Legal Protection. and can also File a lawsuit to the Commercial Court which is a Repressive Legal Protection.